Framing "South Asia" : whose imagined region? - Sinderpal, Singh (2009)
The framing of regions, and in this case 'South Asia', has often been done in ostensibly objective terms. This article argues that far from being an objective exercise, framing regions in general and 'South Asia' in particular, is actually a normative and inherently normative political exercise designed to serve the interests of the 'framers'. The proposition, more specifically, is that the act of framing, in this particular context of 'South Asia', is the imposition of a particular kind of knowledge-as-power in which various peoples and complex ways of life are reduced to essentialist categories and meanings in order that they can be more easily managed and controlled by major regional and global actors. To demonstrate this, the bases of region framing used in the literature are discussed briefly and the manner in which these base have been utilised in the framing of an 'objective' South Asian region is illustrated. The historical record is examined and a continuity is shown between the way the British colonial 'mapping' of South Asia was carried out to demonstrate the 'naturaless' of British imperial domination and the manner in which the independent Indian state has sought to frame 'South Asia' to 'prove' its 'natural hegemony' within South Asia. The conclusion suggests that there may be greater need to fuse theory and the analysis of the 'region' in order to come to a more profound understanding of the salience of the regional level of inquiry in international relations today.